Demonstration of Non-Gaussian Restricted Diffusion in Tumor Cells Using Diffusion Time-Dependent Diffusion-Weighted Magnetic Resonance Imaging Contrast - Hope, Tuva R.; White, Nathan S.; Kuperman, Joshua; Chao, Ying; Yamin, Ghiam; Bartch, Hauke; Schenker-Ahmed, Natalie M.; Rakow-Penner, Rebecca; Bussell, Robert; Nomura, Natsuko; Kesari, Santosh; Bjørnerud, Atle; et al. (Frontiers in Oncology, 2016)
The diffusion weighted imaging (DWI) technique enables quantification of water mobility for probing microstructural properties of biological tissue, and has become an effective tool for collecting information about the underlying pathology of cancerous tissue. Measurements using multiple b-values have indicated a bi-exponential signal attenuation, ascribed to “fast” (high ADC) and “slow” (low ADC) diffusion components. In this empirical study, we investigate the properties of the diffusion time (∆) - dependent components of the diffusion-weighted (DW) signal in a constant b-value experiment. A Xenograft GBM mouse was imaged using ∆ = 11 ms, 20 ms, 40 ms, 60 ms and b=500-4000 s/mm2 in intervals of 500s/mm2. Data was corrected for EPI distortions and the ∆-dependence on the DW signal was measured within three regions of interest (intermediate- and high-density tumor regions and normal appearing brain tissue regions (NAB)). In this empirical study we verify the assumption that the slow decaying component of the DW-signal is non-Gaussian and dependent on ∆, consistent with restricted diffusion of the intracellular space. As the DW-signal as a function of ∆ is specific to restricted diffusion, manipulating ∆ at constant b-value (cb) provides a complementary and direct approach for separating the restricted from the hindered diffusion component. Our results show that only tumor tissue signal of our data demonstrate ∆-dependence, based on a bi-exponential model with a restricted diffusion component, we successfully estimated the restricted ADC, signal volume fraction and cell size within each tumor ROI.